Microbiological Control of UHT Sterilized Milk and Milk Products and Effects on Consumers' Health in Western Algeria - Benyagoub, Elhassan; Ayat, Mohammed; Belarbi, Djamila (Microbes and Health, 2014)
The present study focused on the analysis of microbiological quality of various milk samples such as ultra-high temperature sterilized milk (UHT), melted cheese and yoghurt, obtained from dairy product factories in western Algeria. Hazards identification and development of a quality management standard for these subsidiaries evidenced that the sanitary quality was satisfactory. The result revealed detection of faecal origin contamination total and fecal coliforms in both the yoghurt product and sample of melted cheese where the average content was(1.29±6.72-0.14±0.56 x 103cfu/g) and (0.14±0.6-0.022±0.275 x 103cfu/g) respectively. It is indicative that all samples were free from Staphylococcus aureus and Salmonella sp. The study demonstrated that prerequisite programs (PRP) will prevent the occurrence of microbiological hazards origin, which confirms the fact that hygiene measures are the best safety assurance. The hazard analysis of the production process of yoghurt and cheese allowed us to find out their causes, adoption of preventive measures for certain sensitive stages where hazards can be eliminated or reduced at acceptable levels, the determination of critical control points (CCP)and operational prerequisite programs PRPo, implementing critical limits, and monitoring plans. DOI: http://dx.doi.org/10.3329/mh.v3i1.19777 Microbes and Health, June 2014. 3(1): 21-24